DNA‐Based Synthetic Growth Factor Surrogates with Fine‐Tuned Agonism. Issue 42 (29th July 2021) - Akiyama, Momoko; Ueki, Ryosuke; Yanagawa, Masataka; Abe, Mitsuhiro; Hiroshima, Michio; Sako, Yasushi; Sando, Shinsuke
Abstract: Designing synthetic surrogates of functional proteins is an important, albeit challenging, task in the field of chemistry. A strategy toward the design of synthetic agonists for growth factor or cytokine receptors that elicit a desired signal activity has been in high demand, as such ligands hold great promise as safer and more effective therapeutics. In the present study, we used a DNA aptamer as a building block and described the strategy‐guided design of a synthetic receptor agonist with fine‐tuned agonism. The developed synthetic partial agonist can regulate therapeutically relevant cellular activities by eliciting fine‐tuned receptor signaling. Abstract : A new strategy toward the design of synthetic agonists that elicit a desired signal activity is reported. Synthetic growth factor surrogates showing fine‐tuned agonism were developed by exploiting the programmability of DNA aptamer. These DNA‐based agonists can be used to regulate therapeutically relevant cellular activities by eliciting moderate receptor signaling.